PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN TANGGUNG JAWAB DAN HASIL BELAJAR SISWA KELAS 2 SD - Arista Khoirul Mungzilina; Firosalia Kristin; Indri Anugraheni (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2018)
This study aims to a) describe the steps of applying the Problem Based Learning (PBL) model of learning in improving the responsibility and learning outcomes of second grade students of SDN Panjang 02 Ambarawa.Further, this study wanted b) to know the application of Problem Based Learning (PBL) learning model in increasing the responsibility of 2nd grade students of SDN Panjang 02 Ambarawa. Even more c) to know the application of Problem Based Learning (PBL) learning model in improving the learning outcomes of 2nd grade students of SDN Panjang 02 Ambarawa. Classroom Action Research was conducted at SDN Panjang 02 Ambarawa, data collection techniques used were observations, questionnaires, and tests. The data obtained were analyzed by using quantitative data analysis. The result of the research indicated the responsibility of the students on the initial condition no students including criteria Very Responsible, 15 students (39,5%) including Responsible, 18 students (47,4%) including Responsible enough, 5 students (13,1% %) including Unresponsible, and no students belonging to the Very Unresponsible criteria. Therefore students who are at least accountable enough 33 students with a percentage of 86.8%, then there was an increased in the final condition that there are only students who are on criteria Very Responsible 16 students (42.1%), and Responsible criteria 22 students 57.9%). So that the minimum student responsible enough increased to 38 students with 100% percentage. Results of learning conditions of the initial load of Indonesian language that completed 50% with an average value of 72.1, the first cycle increased to 55.3% with an average of 74.5, cycle II increased again to 100% with an average of 81.1 . Then on the load of PPKn the initial condition was completed 47,4% average 70,7, in the first cycle increased to 52,6% with average 80,3, then cycle II increased again to 100% with average 90 , 1. While the initial Mathematical content of 39.5% complete with an average value of 69.2, the first cycle increased to 47.4% with an average of 72, then cycle II increased again to 100% with an average of 81.6.